Assessment of the consequences of deficiencies in design documents in Saudi Arabia. (4th July 2019) - Abdallah, Abdullatif; Assaf, Sadi; Hassanain, Mohammad A.
ABSTRACT: Properly prepared design documents are crucial to the success of construction projects. Poor design documents can have a range of adverse effects on various construction project stakeholders. This research explored the significance of various consequences of Design Documents' Deficiencies (DDDs) on large construction projects. A comprehensive literature review, and questionnaire survey were conducted. Overall, 15 consequences were identified. Based on responses from 41 designers and 30 contractors, a significance index was assigned to each of the identified consequences of DDDs. The most significant consequences of DDDs were 'design changes' and 'frequent change orders', respectively. The test of agreement revealed a moderate-high level of agreement between designers and contractors. The findings were used to recommend an action plan for preventing the occurrence of DDDs. It is envisioned that this research will increase the awareness of the consequences of DDDs, and hence, contribute to their reduction. The study contributes to the literature by identifying various consequences of DDDs from diverse sources and synthesizing them into a single study. The study also provides separate and combined viewpoints of two key stakeholders of construction projects on the impact DDDs can have on themselves, and the project as a whole. The study contributes to the literature by identifying the various consequences of DDDs in a fast-growing economy in which minor design errors can translate to substantial financial losses. Further, the identified consequences can be employed as performance measures for assessing an organizations' progress towards continuous improvement of their design practice.